Functional analysis of CqPORB in the regulation of chlorophyll biosynthesis in Chenopodium quinoa - Li, Chao; Ran, Minyuan; Liu, Jianwei; Wang, Xiaoxiao; Wu, Qingbing; Zhang, Qiang; Yang, Jing; Yi, Feng; Zhang, Heng; Zhu, Jian-Kang; Zhao, Chunzhao (Frontiers in Plant Science, 2022)
Protochlorophyllide oxidoreductase (POR) plays a key role in catalyzing the light-dependent reduction of protochlorophyllide (Pchlide) to chlorophyllide (Chlide), and thus promotes the transit from etiolated seedlings to green plants. In this study, by exploring ethyl methanesulfonate (EMS)-mediated mutagenesis in Chenopodium quinoa NL-6 variety, we identified a mutant nl6-35 that displays faded green leaf and reduced chlorophyll (Chl) and carotenoid contents. Bulk segregant analysis (BSA) revealed that a mutation in CqPORB gene is genetically associated with the faded green leaf of the nl6-35 mutant. Further study indicates that the nl6-35 mutant exhibits abnormal grana stacks and compromised conversion of Pchlide to Chlide upon illumination, suggesting the important role of CqPORB in producing photoactive Pchlide. Totally three CqPOR isoforms, including CqPORA, CqPORA-like, and CqPORB are identified in NL-6 variety. Transcriptional analysis shows that the expression of all these three CqPOR isoforms is regulated in light- and development-dependent manners, and in mature quinoa plants only CqPORB isoform is predominantly expressed. Subcellular localization analysis indicates that CqPORB is exclusively localized in chloroplast. Together, our study elucidates the important role of CqPORB in the regulation of Chl biosynthesis and chloroplast development in quinoa.